In vitro studies on protective effect of Glycyrrhiza glabra root extracts against cadmium-induced genetic and oxidative damage in human lymphocytes - (:unkn) unknown (SPRINGER, 2014)
Cadmium is a modern environmental contaminant that is toxic and carcinogenic. Glycyrrhiza glabra is a traditional medicinal herb which grows in the various parts of the World. Recent studies demonstrated that G. glabra has antifungal, antimicrobial, antioxidant, and powerful antiinflammatory features. The purpose of this study was to investigate the genetic safety of extracts from G. glabra and its effects on cadmium (as CdCl2) induced genotoxicity. Therefore we evaluated the capability of G. glabra extract to inhibit the rate of micronucleus (MN), sister chromatid exchange (SCE) formations induced by CdCl2. Moreover, to assess the effects of G. glabra on cell viability and oxidative status, we performed 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) and total antioxidant capacity (TAC) assays. Our results showed that there were significant increases (P\0.05) in both SCE and MN frequencies of cultures treated with CdCl2 (5 ppm) as compared to controls. However, co-application of G. glabra extract (5, 10 and 20 ppm) and CdCl2 resulted in decreases of MN and SCE rates as compared to the group treated with CdCl2 alone. Again, the results of MTT and TAC assays clearly indicated dose dependent ameliorative effects of G. glabra extracts against CdCl2 toxicity. In conclusion, this study demonstrated for the first time that G. glabra extracts provided increased resistance of DNA against CdCl2 induced genetic and oxidative damage in human lymphocytes. So, the risk on target tissues of CdCl2 could be reduced and ensured early recovery from its toxicity.
Keywords: Cadmium; Glycyrrhiza glabra; Genotoxicity; Human lymphocytes; Oxidative stress; Protective effect; INDUCED DNA; TOXICITY; LICORICE; ANTIOXIDANT; STRESS; GENOTOXICITY; ABERRATIONS; MECHANISMS; LEAVES; CELLS